Conserved Amino Acid Moieties of Candidatus Desulforudis audaxviator MazF Determine Ribonuclease Activity and Specificity - Tamiya-Ishitsuka, Hiroko; Tsuruga, Masako; Noda, Naohiro; Yokota, Akiko (Frontiers in Microbiology, 2021)
The toxin-antitoxin (TA) system, inherent to various prokaryotes, plays a critical role in survival and adaptation to diverse environmental stresses. Toxin MazF, belonging to the type II TA system, functions as a sequence-specific ribonuclease that recognizes 3 to 7 bases. In recent studies, crystallographic analysis of MazFs from several species suggested the presence of amino acid sites important for MazF substrate RNA binding and catalytic activity. Herein, we characterized MazF from Candidatus Desulforudis audaxviator (MazF-da) and identified key amino acid residues for its catalytic function. MazF-da, expressed using a cell-free protein synthesis system, is a six-base-recognition-specific ribonuclease that preferentially cleaves UACAAA sequences and weakly cleaves UACGAA and UACUAA sequences. We also found that the optimum temperature for MazF-da activity is around 60°C. Analysis using mutants with a single mutation at an amino acid residue site that is well conserved among multiple MazFs showed that G18, E20, R25, and P26 are important for the ribonuclease activity of MazF-da. The recognition sequence of the N36A mutant differed from that of the wild type. This mutant cleaved UACAAG in addition to UACAAA, but did not cleave UACGAA or UACUAA, suggesting that Asn36 affects the loosening and narrowing of MazF-da cleavage sequence recognition. Our study reveals UACAAA as the recognition sequence of MazF-da and provides insight into the amino acid sites that are key to its unique enzymatic properties.